Production and acceptance of gamma-aminobutyric acid (GABA)-Kimchi using Tetragenococcus halophilus and Monosodium Glutamate - Fateen Aqlima Haniem Ab Jabar; Chong, Shin Yee; Zul Ilham; Nurul Aqilah Mohd Zaini; Muhamad Hafiz Abd Rahim; Nur Asyiqin Zahia-Azizan; Wan Abd Al Qadr Imad Wan-Mohtar (Penerbit Universiti Kebangsaan Malaysia, 2025)
The addition of gamma-aminobutyric acid (GABA) to fermented foods has been progressively expanded to produce ‘Superfood’. In this study, Tetragenococcus halophilus was extracted from soy sauce moromi from local factory and evaluated for its potential of Gamma-Aminobutyric Acid (GABA) production in kimchi fermentation. There were four different formulations that were fermented for 20 days. Kimchi fermentation was performed on kimchi added with Monosodium Glutamate (MSG) (T1), kimchi inoculated with T. halophilus (T2), kimchi with combined MSG and T. halophilus (T3), and plain kimchi with no additional starter as a control (C), respectively. A spectral HPLC analysis confirmed that the control sample (C) obtained the highest GABA with 10.90 mg/L followed by T2 with 6.02 mg/L, T1 with 5.72 mg/L, and the lowest content of GABA is produced by T3 with 3.74 mg/L. Sensory analysis was performed by a total of 50 panellists examined the colour, flavour, texture, taste, and overall acceptance of kimchi samples. Kimchi with MSG (T1) received the highest scores for overall acceptance including flavour and taste. This study demonstrated the development of GABA-kimchi using T. halophilus and MSG as future food comprising substantial nutritional profile and improved sensory characteristics.